2023
DOI: 10.3847/2041-8213/accada
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Dynamics of Strongly Twisted Magnetar Magnetospheres: Kinking Flux Tubes and Global Eruptions

Abstract: The origins of the various outbursts of hard X-rays from magnetars (highly magnetized neutron stars) are still unknown. We identify instabilities in relativistic magnetospheres that can explain a range of X-ray flare luminosities. Crustal surface motions can twist the magnetar magnetosphere by shifting the frozen-in footpoints of magnetic field lines in current-carrying flux bundles. Axisymmetric (2D) magnetospheres exhibit strong eruptive dynamics, i.e., catastrophic lateral instabilities triggered by a criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…This situation is loosely similar to the polar flaring dynamics of magnetar explosions (Parfrey et al 2013;Carrasco et al 2019). For these, Mahlmann et al (2023) have recently shown that depending on the latitude of the footpoint of the twisted flux tube, it will either flare or become kink unstable, thereby dissipating part of the twist. The distinction between the two states directly results from the different locations inside the magnetosphere that experience the twist.…”
Section: Importance Of Magnetic Field Inclinationmentioning
confidence: 65%
“…This situation is loosely similar to the polar flaring dynamics of magnetar explosions (Parfrey et al 2013;Carrasco et al 2019). For these, Mahlmann et al (2023) have recently shown that depending on the latitude of the footpoint of the twisted flux tube, it will either flare or become kink unstable, thereby dissipating part of the twist. The distinction between the two states directly results from the different locations inside the magnetosphere that experience the twist.…”
Section: Importance Of Magnetic Field Inclinationmentioning
confidence: 65%
“…In addition to sudden quakes, the crust may flow plastically and slowly twist a magnetospheric flux bundle to an instability threshold. Three-dimensional simulations of this process demonstrate that relaxation of the unstable flux bundle generates fast magnetosonic waves in the magnetosphere (Mahlmann et al 2023).…”
Section: Mhd Waves From Quakesmentioning
confidence: 99%
“…In the hybrid scenario, Most & Quataert (2023) demonstrated how the differentially rotating HMNS builds loops with footpoints at different latitudes on its surface. The resultant twist in the loop causes it to become unstable, inflate, and buoyantly rise, forming a bubble that is entirely detached from the HMNS surface and erupts after reconnecting (e.g., Carrasco et al 2019;Mahlmann et al 2023;Most & Quataert 2023). This behavior powers quasiperiodic flares prior to the jet formation.…”
Section: Precursor Flarementioning
confidence: 99%